A Systematic Review on Harmful Alcohol Use Among Civilian Populations Affected by Armed Conflict in Low- and Middle-Income Countries. (19th September 2017) - Lo, Janice; Patel, Preeti; Shultz, James M.; Ezard, Nadine; Roberts, Bayard
ABSTRACT: Background : There are currently over 55 million refugees and internally displaced persons due to armed conflict. In addition, there are around 150 million more conflict-affected residents who remain in their home communities. Armed conflict poses a number of potential risks for harmful alcohol use. Objective : The objective of the study was to systematically examine evidence on harmful alcohol use among conflict-affected populations in low- and middle-income countries. Methods : A systematic review methodology was used following PRISMA guidelines. Quantitative studies were selected with outcomes relating to harmful alcohol use among conflict-affected populations in low- and middle-income countries. Seven bibliographic databases and a range of gray literature sources were searched. Descriptive analysis was applied and a quality assessment conducted using the Newcastle-Ottawa Quality Assessment Scale. Results : The search yielded 10, 037 references of which 22 studies met inclusion criteria. Twenty-one of the studies used a cross-sectional design, and 1 used a case series design. Evidence on risk factors for harmful alcohol use was weak overall. Factors associated with harmful alcohol use were male gender, older age, cumulative trauma event exposure, and depression. There were no studies on the effectiveness of interventions for harmful alcohol use. The strength of evidence was also limited by the generally moderate quality of the studies. Conclusions : Substantially more evidence is required to understand the scale of conflict-associated harmful alcohol use, key risk factors, association of alcohol use with physical and mental disorders, and effectiveness of interventions to address harmful alcohol use in conflict-affected populations.